[Distant interactions between enhancers and promoters in Drosophila melanogaster are mediated by transgene-flanking Su(Hw) insulators]. - Davydova, A.I.; Erokhin, M.M.; Georgiev, P.G.; Chetverina, D.A. (Genetika, 2011)
Insulators are DNA elements modulating gene activation by enhancers. Interaction between insulators can result in either isolation, or activation of promoter by the enhancer. In the present study, it is demonstrated that in transgenic lines, the yellow enhancers are unable to activate promoter of the tagged gene through the mini-white gene. The mini-white promoter, which functions as an insulator, can block the enhancer activity. In case that the genes and regulatory elements in the construct are flanked by Su(Hw) insulators from retroposon MDG4, interaction between enhancers and the yellow promoter is restored. The data obtained are congruent with the model suggesting that promoters can function as insulators, and that interaction between the insulators facilitates the interaction between enhancers and promoters within transcriptional domain.